(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
The utilization of minerals in cosmetic formulations has been a longstanding tradition, with Yashada Bhasma (zinc oxide) emerging as a prominent ingredient in modern sunscreen formulations due to its remarkable properties. This article provides a comprehensive examination of Yashada Bhasma historical significance, chemical composition, and therapeutic attributes as described in classical literature. The scientific analysis validates its efficacy as a physical barrier against UVA and UVB radiation, highlighting its photostability and compatibility with sensitive skin. Structural and chemical characterization techniques illuminate its nano-scale transformation during the purification process, enhancing its effectiveness. Comparative analyses with other sunscreen ingredients emphasize its superiority in terms of UV protection spectrum, skin compatibility, and regulatory approval. A market survey reveals the widespread incorporation of Yashada Bhasma into various Ayurvedic and herbal cosmetic products, reflecting its acceptance and popularity among consumers. Overall, this article bridges the gap between Classical wisdom and scientific validation, showcasing Yashada Bhasma as a versatile and effective component in sunscreen formulations, poised to meet the evolving needs of skincare and sun protection in contemporary times.